Pengaruh terapi okupasi hidroponik terhadap tingkat harga diri penerima manfaat di unit rehabilitasi sosial eks psikotik - Romadhan, Robi; Estria, Suci Ratna; Etlidawati, Etlidawati; Prasetya, Rikhan Luhur (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Mental health issues encompass a range of challenges, such as schizophrenia disorders that are often associated with decreased self-esteem in individuals. Patients with schizophrenia who have low self-esteem exhibit poor self-perception, feelings of worthlessness, and lack of self-confidence. Occupational therapy, as an effective non-pharmacological intervention, can improve self-esteem through targeted activities. Purpose: To assess the effect of hydroponic occupational therapy intervention on the level of self-esteem of beneficiaries in a social rehabilitation unit for ex-psychotics. Method: Pre-experimental one group pretest-posttest design, conducted on beneficiaries who experience low self-esteem at the Social Rehabilitation Unit for Ex-Psychotics